ChatGPT-4o Answer Accuracy Analysis for Biology Test Questions - Fernando, Adam; Anggun, Diah Putri (Bioeducation Journal, 2024)
One of the products of current technological developments is artificial intelligence (AI). ChatGPT is one of the AI ​​products that is widely used, including educators and students. Lecturers are required to develop learning that supports improving students' critical thinking skills. Students often use shortcuts to find answers or solutions related to problems presented by lecturers in class, including using ChatGPT. However, the answers given by ChatGPT are not entirely correct, so it is necessary to verify the explanation. This descriptive study was conducted by directly testing the answers generated by ChatGPT-4o. The answers are explained through literature studies from various textbooks or scientific articles related to biology. The instrument used was in the form of test questions related to several topics of courses in the field of biology education, which were typed as prompts to obtain answer information from ChatGPT-4o. The results of the answers to each question typed into ChatGPT were then analyzed using scoring based on the assessment rubric. Based on the results, it can be concluded that ChatGPT-4o's answers accuracy on biology test are fairly accurate.